ANALISIS DAMPAK PEMBERIAN KREDIT MODAL KERJA TERHADAP PENINGKATAN PENDAPATAN USAHA KECIL PADA PT. BPR DELTA ARTHA PANGGUNG SITUBONDO - Hali Makki (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
Bank Perkredit Rakyat (BPR) has a variety of savings products and credit products. One of its credit products is a working capital credit product. This working capital is a business capital financing credit / business operations. This research is in the form of field research or also known as qualitative research. The results showed that the procedure for disbursing working capital loans at PT. BPR Delta Artha Panggung Situbondo Branch is not complicated and the requirements required are easy to meet by small businesses, small entrepreneurs also feel no objection to the guarantee required by PT. BPR Delta Artha Panggung Situbondo Branch to take working capital credit, so that the distribution of working capital credit product funds from PT. BPR Delta Artha Panggung Situbondo Branch is deeply felt by small entrepreneurs who lack capital, because with the funds for working capital products, small entrepreneurs can be more free to add a variety of their business products.